Trends in the development of the Russian asset management industry - E. I. Kulikova; B. B. Rubtsov (Путеводитель предпринимателя, 2020)
The authors analyze the problems ofdevelopment of Russian asset management industry, namely the market of pension savings and determine the directions of its improvement.